Antihypertensive therapy adherence, treatment and healthy lifestyle of hypertensive patients from Northern Portugal - Pinto, Isabel C. (2016)
Hypertension is among the non-communicable chronic diseases most prevalent in the world. The antihypertensive therapy adherence is important to control hypertension. Objectives: To characterize the pharmacological treatment of hypertensive patients from northern Portugal, estimate the prevalence of antihypertensive therapy adherence and related factors. Methods: This correlational and cross-sectional study was based on a questionnaire, with MAT, FFQ for sodium and IPAQ scales to acess the therapy adherence, eating habits and physical activity, respectively. It was applied to 385 hypertensive patients from northern Portugal. It was used descriptive statistics and Chi-Square test, with a significance level of 5%. Results: The sample consisted mostly of females (70.8%), between 19 and 94 years old, with an average age of 62 years. Angiotensin II receptor antagonist (ARA) are the pharmalogical group more used (33.5%). Regarding the consumption of sodium, the most consumed foods were cod, sausages, patties, canned and ham. Most respondents (50.9%) practicing vigorous and/or moderate physical activity. The prevalence of therapy adherence was 93.2%, and more adherent are people aged over 50 years (p=0.003), in active working or retired (p<0.001). Conclusions: The participants of this study present unhealthy eating habits, but overall are physically active. They shows a high prevalence of antihypertensive therapy adherence, among active working or retired people.